Types of Code-Switching in Kompas Newspaper : A Study in Political and Law Articles - Ambarita, Esron; Meliala, Grace Cya Aprilia S (Journal of Applied Linguistics, 2024)
This study aimed to investigate code-switching patterns in political and law articles in Kompas newspaper, one of the leading national newspapers in Indonesia with the highest editorial quality from an Indonesian perspective. This study is limited to political and law articles by conducting an in-depth descriptive analysis to clarify the types of code-switching using Gumperz's (1977) theory. Data were randomly selected for 4 months, from January 1, 2010, to April 30, 2010, for 16 editions. This study uses a qualitative descriptive method. The results show that there are 4 types of code-switching in political and law articles in Kompas newspaper, i.e., (1) metaphorical code-switching, (2) conversational code-switching, (3) interstitial code-switching, and (4) intrasentential code-switching. Situational code-switching and tag-switching were not found in this study. Four out of six sub-types of conversational code-switching were found, i.e., (i) interjection, (ii) reiteration, (iii) message qualification, and (iv) personalization vs objectivizations. On the other hand, two sub-types of conversational code-switching, namely quotations and address specifications, were not found. Keywords: Code_Switching; Kompas_ Newspaper; Political and Law Articles